Molecular dynamics study of water vapor condensation on a composite wedge-shaped surface with multi wettability gradients. (June 2019) - Xu, Bo; Chen, Zhenqian
Abstract: To find out whether the composite wedge-shaped surface with multi wettability gradients could accelerate the condensate drainage in a micro view, the model of water vapor condensation on such surface was built and studied by molecular dynamics (MD). The vertex angle and wettability gradient of wedge-shaped surface were investigated to obtain the best condition for accelerated removal of condensate. The wettability gradient of two surfaces was divided into three groups: Group A (hydrophilic - super hydrophilic), Group B (hydrophobic - hydrophilic) and Group C (hydrophobic - super hydrophobic). The vertex angle was changed from 7°, 10°, 14° to 20°. Filmwise condensation (FWC) appeared in Group A and dropwise condensation (DWC) formed in Group B. However, there was no condensation in Group C. Although the FWC in Group A could drain, the drainage rate was slow. Only in Group B, the DWC could form water droplet and the movement of droplet could be controlled by the wedge-shaped surface, which was helpful for condensate drainage. When comparing the effect of different vertex angle, the smaller vertex angle could finish the FWC more quickly in Group A due to the smaller area of the super hydrophilic surface. In group B, small wedge-shaped surface would take more time to form main nuclei, while large wedge-shaped surface forming two nuclei also took more time to form a whole nanoscale droplet. In that case, DWC rate was quicker and condensation drainage was better in vertex angle of 14° in these four conditions.